Barreras al acceso a la justicia en el acoso laboral (2014)
In Colombia, Law 1010, 2006, regulates the correction, prevention, and penalization of mobbing. In spite of the law, in practice it is not very effective the access to justice for victims of mobbing, as evidenced in few denounces andfew penalizing sentences. In this reflection article, juridical and material barriers which prevent the access to justice in mobbing are analyzed, which results are part of the project “Practices of Mobbing and the way how they are solved in ajuridical way Colombia,” carried out by Sociology and Jurisprudence researchers of Universidad del Rosario